Anatomical knowledge retention & interventional strategies in nursing education - Neumeier, Melanie; Narnaware, Yuwaraj (My University, 2019)
Creating experiential learning opportunities to improve knowledge acquisition and retention is a common goal in post-secondary education, but it may not be clear how to start. In this presentation, we discuss how to develop and use a knowledge retention study to identify gaps in learning and implement targeted learning strategies.
Presented April 30 - May 1, 2019 at the University of Calgary Conference on Postsecondary Learning and Teaching: Exploring Experiential Learning held in Calgary, Alberta.
Keywords: knowledge retention; students; postsecondary education